A Study of an Experimental Design Methodology for the Removal of Cadmium from Polluted Wastewater via the Electrocoagulation Process using Solar Energy - Boulanouar, Lissir; Louhichi, Boulbaba; Mabrouk, Abdelkader; Salem Abdennaji, Tarek; Hamdi, Wissem; Hamdi, Noureddine; Ammar, Houas (Engineering, Technology & Applied Science Research, 2025)
The aim of this study was to optimize several parameters that affect the Electrocoagulation (EC) process of Cadmium (Cd) from polluted wastewater. To estimate the contribution of each parameter to the overall removal process, an experimental design methodology was employed. System performance was optimized using Response Surface Methodology (RSM), focusing on key factors, such as pH, amperage, and salt (NaCl) concentration. Minitab 19 software was utilized to develop a full model equation, including the main effects and interactions between the variables. The analysis revealed that pH and amperage were the most influential factors, contributing 43.04% and 26.27%, respectively, to system efficiency. The optimal parameter range for achieving a yield (above 95%) was identified through response contour plots and interaction analyses: pH ranged between 6.9 and 11, amperage between 300 and 500 mA, and salt concentration between 0.1 and 0.6 g/L. Further refinement of these ranges was visualized using response surface diagrams and the Box-Behnken design. Practical experiments were conducted using the optimized values (pH = 6.2, amperage = 280 mA, salt = 0.46 g/L), and the results were compared to the theoretical model. A minimal error margin of less than 2% between the practical and statistical results validated the model’s accuracy.